OFF-LABEL PRESCRIBING. POSSIBLE CAUSES, TYPES AND CONSEQUENCES. LEGAL REGULATION IN THE RUSSIAN FEDERATION - S. Yu. Martsevich; A. R. Navasardjan; N. A. Komkova (Столичная издательская компания, 2017)
The off-label prescribing is multifaceted problem and affects  the interests and scope  of activities of different parties. Possible reasons, types of offlabel use of drugs are given in the article, as well as legal regulation of this issue in the Russian Federation and abroad. Such type of prescriptions is broad in various fields of medicine, especially in pediatrics, oncology, obstetrics and gynecology. Often this is due to the inability to perform appropriate randomized clinical studies, because of regulatory difficulties, economic inexpediency and ethical considerations. An additional complication in regulating this process is the fact that in the Russian Federation there is no clear legal basis for the off-label use of drugs,  as well as the fact that clinical recommendations do not have a legal status. It seems relevant to study the assessment of the consequences of off-label drugs use, especially long-term effects. For this purpose, it seems important to use existing medical registers, as well as to create new prospective registers devoted to the study of the consequences of off-label prescribing.